Frequency of exercise-induced ST-T-segment deviations and cardiac arrhythmias in recreational endurance athletes during a marathon race: results of the prospective observational Berlin Beat of Running study. Issue 8 (3rd August 2017) - Herm, Juliane; Töpper, Agnieszka; Wutzler, Alexander; Kunze, Claudia; Krüll, Matthias; Brechtel, Lars; Lock, Jürgen; Fiebach, Jochen B; Heuschmann, Peter U; Haverkamp, Wilhelm; Endres, Matthias; Jungehulsing, Gerhard Jan; et al.
Abstract : Objectives: While regular physical exercise has many health benefits, strenuous physical exercise may have a negative impact on cardiac function. The 'Berlin Beat of Running' study focused on feasibility and diagnostic value of continuous ECG monitoring in recreational endurance athletes during a marathon race. We hypothesised that cardiac arrhythmias and especially atrial fibrillation are frequently found in a cohort of recreational endurance athletes. The main secondary hypothesis was that pathological laboratory findings in these athletes are (in part) associated with cardiac arrhythmias. Design: Prospective observational cohort study including healthy volunteers. Setting and participants: One hundred and nine experienced marathon runners wore a portable ECG recorder during a marathon race in Berlin, Germany. Athletes underwent blood tests 2–3 days prior, directly after and 1–2 days after the race. Results: Overall, 108 athletes (median 48 years (IQR 45–53), 24% women) completed the marathon in 249±43 min. Blinded ECG analysis revealed abnormal findings during the marathon in 18 (16.8%) athletes. Ten (9.3%) athletes had at least one episode of non-sustained ventricular tachycardia, one of whom had atrial fibrillation; eight (7.5%) individuals showed transient ST-T-segment deviations. Abnormal ECG findings were associated with advanced age (OR 1.11 per year, 95% CI 1.01 to 1.23), while sex and cardiovascular risk profile had no impact. Directly after the race, high-sensitive troponin T was elevated in 18 (16.7%) athletes and associated with ST-T-segment deviation (OR 9.9, 95% CI 1.9 to 51.5), while age, sex and cardiovascular risk profile had no impact. Conclusions: ECG monitoring during a marathon is feasible. Abnormal ECG findings were present in every sixth athlete. Exercise-induced transient ST-T-segment deviations were associated with elevated high-sensitive troponin T (hsTnT) values. Trial registration: ClinicalTrials.gov NCT01428778 ; Results.